Joko Widodo’s Digital Diplomacy: A Prospect and Challenge for Indonesia’s Digital Diplomacy towards Middle Power - Sasha Syaifani; Naaimatur Rofiani Qubba (Universitas Airlangga, 2017)
Indonesia is known as a country whose people massively use social media. It is currentlyone of the largest internet users in the world, especially social media. President of Indonesia,Joko Widodo, (famously called ‘Jokowi’) also tries to ‘fit in’ to the trend of social media acrossIndonesia. Jokowi has several social media accounts, including Facebook, Twitter, Instagram,and YouTube. He even publishes a lot of his works, including his meeting agenda with otherstates’ leaders. Jokowi sometimes uploads some video blogs or ‘vlogs’ which some of them arecollaborations with leaders of powerful countries, such as King Salman Abdul Aziz of SaudiArabia, Emmanuel Macron of France, and many others. Therefore, the authors consider thisas a great opportunity for Indonesia to start digital diplomacy. Through literature study,the authors will provide a broader analysis of prospect and challenge of Indonesia’s digitaldiplomacy. The findings showed that digital diplomacy implemented by Jokowi has a goodprospect albeit many challenges. Moreover, it was also discovered that this type of diplomacycould bring some threats to Indonesia.